2003
DOI: 10.1128/aac.47.11.3653-3656.2003
|View full text |Cite
|
Sign up to set email alerts
|

G484S Amino Acid Substitution in Lanosterol 14-α Demethylase ( ERG11 ) Is Related to Fluconazole Resistance in a Recurrent Cryptococcus neoformans Clinical Isolate

Abstract: Five sequential Cryptococcus neoformans isolates recovered from an AIDS patient with recurrent meningitis were analyzed. Four isolates were fluconazole susceptible, while the fifth isolate developed fluconazole resistance. Analysis of the 14-␣ lanosterol demethylase gene (ERG11) showed a point mutation in the resistant strain responsible for the amino acid substitution G484S.Mechanisms of azole resistance already described for yeasts include altered affinity of lanosterol 14-␣ demethylase (ERG11) to azole drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 13 publications
1
112
0
3
Order By: Relevance
“…A few studies have examined the roles of the cryptococcal ERG11 gene and of the ATP-binding cassette transporters in resistance in C. neoformans (377)(378)(379)(380); whether these observations are applicable to C. gattii are uncertain. Mutations in, or overexpression of, the ERG11 gene, encoding the azole target lanosterol 14-␣ demethylase, and overexpression of one or more plasma membrane proteins that pump azoles out of the cell are well recognized mechanisms by which fungi acquire resistance to azoles (379).…”
Section: Mechanisms Of Azole Resistance In C Gattiimentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have examined the roles of the cryptococcal ERG11 gene and of the ATP-binding cassette transporters in resistance in C. neoformans (377)(378)(379)(380); whether these observations are applicable to C. gattii are uncertain. Mutations in, or overexpression of, the ERG11 gene, encoding the azole target lanosterol 14-␣ demethylase, and overexpression of one or more plasma membrane proteins that pump azoles out of the cell are well recognized mechanisms by which fungi acquire resistance to azoles (379).…”
Section: Mechanisms Of Azole Resistance In C Gattiimentioning
confidence: 99%
“…The latter isolate contained a point mutation responsible for the amino acid substitution G484S (377). However, the possibility of another mechanism of resistance was not excluded.…”
Section: Mechanisms Of Azole Resistance In C Gattiimentioning
confidence: 99%
“…In C. neoformans, the alteration of the azole target Erg11 has been documented for numerous clinical isolates (492,602). Recently, a three-dimensional structure of C. neoformans Erg11 was elucidated, and residues important for its normal enzymatic function as well as those that interact with fluconazole were identified (531).…”
Section: Alteration Of the Drug Targetmentioning
confidence: 99%
“…The G448S amino acid substitution described here corresponds to the G464S substitution in Candida albicans ERG11 and the G484S substitution in Cryptococcus neoformans, both of which are involved in fluconazole resistance (25,27). Several studies have demonstrated that this amino acid substitution detected in C. albicans ERG11 confers a change in the orientation of the P450 heme-binding domain, leading to decreased azole binding and decreased catalytic activity of the enzyme (15,27).…”
mentioning
confidence: 97%